Controlling unsteady cavity flows using internal structures - Knowles, Kevin; Bacci, David; Saddington, Alistair J.; Newby, B.; Taylor, N. J. (La Societe Savante de L'Aeronautique et de L'Espace, 2017)
We report experimental measurements and preliminary analysis on a series of geometric modifications to a rectangular cavity, aimed at alleviating the severity of the aeroacoustic environment. The cavity had a length-to-depth ratio of 5 and a width-to-depth ratio of 1, and featured a simplified representation of a generic missile on the centre line. The modifications consisted of full width and depth ribs or “collars” with a cutout for the missile. Collars could be fitted at various combinations of locations in the cavity and were either straight (i.e. perpendicular to the cavity centre line), leaned or yawed. The cavity flowfield was characterised by surface pressure measurements along the ceiling. Judging from the available measurements the presence of collars modified the mean pressure distribution, and appeared to reduce the acoustic tones and generally lower the broadband noise.